Phytochemical profile and antioxidant properties of the edible and non-edible portions of black sapote (Diospyros digyna Jacq.). (30th June 2022) - Mannino, Giuseppe; Serio, Graziella; Bertea, Cinzia Margherita; Chiarelli, Roberto; Lauria, Antonino; Gentile, Carla
Highlights: The pulp polyphenol content is comparable to the 100 fruits richest in polyphenols. The black sapote seed extract strongly modulates CAT gene expression. The antioxidant activity of the peel is 7-12 fold higher than the edible portion. The 29 identified compounds are variably distributed in the peel, pulp, and seed. A-type proanthocyanidins content in black sapote is higher than B-type ones. Abstract: This study evaluated the phytochemical profile and antioxidative properties of the edible and non-edible portions of black sapote. The phytochemical analysis highlighted the presence of several bioactive compounds, differently distributed among peel, pulp and seeds. In particular, the peel resulted rich of flavan-3-ols and proanthocyanidins, whereas seeds contained high amount of organic acids, including ferulic, citric and sinapic acids. Concerning functional properties, both edible and non-edible portions showed a significant prevention of lipid peroxidation in a cell-based model. Moreover, the results suggested that the antioxidant protection involved both redox active properties and gene expression modulation. Concerning redox active properties, peel extracts showed an antioxidant activity 7/12-fold higher than the edible portion, while seed extracts were more active in increasing catalase gene expression. The obtained results confirmed that black sapote is a good source of antioxidant phytochemicals and its non-edible portions have a great potential in the production of functional foods and supplements.